Evidence and reality: an observational study on pharmacological outcomes in advanced head and neck tumors - Jordán de Luna, Consuelo; Esteve, Anna; Montero Pérez, Olalla; Clopés Estela, Ana; Oliva, Marc; Lozano Borbalas, Alicia; Mesía Nin, Ricard (Frontiers in Oncology, 2025)
The Catalan Institute of Oncology (ICO) is a comprehensive centre for the prevention, diagnosis, and treatment of cancer. At the institute, there is a set of institutional clinical practice guidelines, named ICOPraxis. The field of oncology therapeutics is currently undergoing a transition towards a model of personalised medicine. Institutional clinical guidelines can be more precise in their recommendations by providing a local focus. An evaluation of the utility of clinical guidelines may be conducted through a descriptive analysis of the selection of treatment and the resulting outcome. Retrospective cohort analysis of patients diagnosed with locally-advanced and recurrent/metastatic HNSCC (stage III to IVc according to 7 and 8th edition TNM-AJCC) and treated at the The Head and Neck Cancer Functional Unit of ICO and Bellvitge University Hospital. This study allows us to describe the outcomes of our head and neck tumour patients with real-life data providing information on the possible dilution of the effect when compared to reference clinical trials.